The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1981-5271v43suplemento1-20180192
|View full text |Cite
|
Sign up to set email alerts
|

Estresse em Estudantes ao longo da Graduação Médica

Abstract: RESUMO O estresse corresponde a uma resposta física, psíquica e hormonal que ocorre quando o organismo necessita se adaptar frente a uma situação desafiadora. É uma das respostas mais recorrentes no meio acadêmico devido à rotina exaustiva e conteúdo denso que exigem responsabilidade e competitividade dos estudantes. Na graduação médica, somam-se a estes fatores a preocupação do estudante em aprender o conteúdo discutido em aulas e a pressão exercida pelos próprios acadêmicos, além da cobrança da sociedade. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 6 publications
2
12
1
13
Order By: Relevance
“…The results of this study showed a high number of undergraduate students in Speech, Language, and Hearing Sciences with stress, with a higher prevalence than that found in other studies with university students in the health area (5)(6)(7)(8) and a much higher rate when compared to students from other areas (1,12) .…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…The results of this study showed a high number of undergraduate students in Speech, Language, and Hearing Sciences with stress, with a higher prevalence than that found in other studies with university students in the health area (5)(6)(7)(8) and a much higher rate when compared to students from other areas (1,12) .…”
Section: Discussioncontrasting
confidence: 52%
“…We acknowledge that those levels could be different if the questionnaires were applied at the beginning of the semester, since the end of a semester is the period with a large concentration of tests and activities that need to be completed, therefore, with a greater incidence of stressful events. Regarding the analysis of the stressful scenario in which the students were inserted, the "resistance" phase was predominant, followed by the "almost exhaustion" phase, as observed in similar studies (5)(6)(7)(8) . The results also indicated that, overall, the investigated students displayed psychological techniques to deal with stress, a relationship that can be justified by the fact that the "resistance" phase is the phase of physical and mental rebalancing, with anxiety and social isolation as its main symptoms (13) .…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations